2014
DOI: 10.2106/jbjs.n.00198
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Suture-Button Fixation on Simulated Syndesmotic Malreduction: A Cadaveric Study

Abstract: Although the clinical relevance is unknown, dynamic syndesmotic fixation may mitigate clamp-induced malreduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
70
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(76 citation statements)
references
References 25 publications
4
70
0
2
Order By: Relevance
“…They found that with anterior offaxis clamping, the mean sagittal malreduction was 2.7 ± 2.0 mm with screw fixation and 1.0 ± 1.0 mm with suture button fixation. They also found a difference in posterior off-axis clamping; the sagittal malreduction was 7.2 ± 2.3 mm with screw fixation and .05 ± 1.4 mm with suture button fixation [58]. They concluded that suture button fixation of the syndesmosis results in less postoperative displacement in comparison to the more traditional screw fixation.…”
Section: Operative Treatment For Isolated Syndesmotic Injuriesmentioning
confidence: 97%
See 2 more Smart Citations
“…They found that with anterior offaxis clamping, the mean sagittal malreduction was 2.7 ± 2.0 mm with screw fixation and 1.0 ± 1.0 mm with suture button fixation. They also found a difference in posterior off-axis clamping; the sagittal malreduction was 7.2 ± 2.3 mm with screw fixation and .05 ± 1.4 mm with suture button fixation [58]. They concluded that suture button fixation of the syndesmosis results in less postoperative displacement in comparison to the more traditional screw fixation.…”
Section: Operative Treatment For Isolated Syndesmotic Injuriesmentioning
confidence: 97%
“…Some limited investigations have attempted to compare dynamic suture button fixation with syndesmotic screw fixation [54,[57][58][59][60][61][62]. Westermann et al performed a cadaveric study to see if there was a difference in the malreduction of syndesmotic injuries when comparing screw fixation with tightrope fixation [58].…”
Section: Operative Treatment For Isolated Syndesmotic Injuriesmentioning
confidence: 99%
See 1 more Smart Citation
“…[130][131][132][133][134][135][136][137][138][139][140][141][142][143][144] A hole is drilled through the fibula and tibia, and then a suture is passed through and secured on both ends via a metallic button. Systematic reviews of low levels of clinical evidence have demonstrated similar functional outcomes, with quicker return to work and less frequent need for implant removal.…”
Section: Dynamic Fixationmentioning
confidence: 99%
“…Because of this, dynamic implants have been investigated in malreduced cadaveric models and have been shown to mitigate clamp-induced malreduction in the coronal and sagittal planes. 144 By improving the reduction, the surgeon can hopefully maximize patient outcomes and minimize need for secondary interventions.…”
Section: Surgeon Factorsmentioning
confidence: 99%